Analisis Kebijakan Perlindungan Korban Penipuan Investasi Bodong Melalui Aplikasi XFA AI - Gustiana, Dita; Fauziah; Nilawati; Zuraidah; Pranata, Eka Octavian; Fadhilah, Nabila (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2025)
This research focuses on two issues. First, how is legal protection provided to victims of fraudulent investment schemes through the XFA AI application? Second, what is the perspective of Islamic criminal law on fraudulent investment schemes through the XFA AI application? This research method utilizes library research, a type of normative juridical research. The collected data was analyzed descriptively and qualitatively, examining legal norms found in laws and regulations, as well as norms that emerge and develop within society. The results of this study conclude that: Legal protection for victims of fraudulent investment schemes through the XFA AI application can be implemented both preventively and repressively. Preventive efforts are implemented through education, supervision, and complaint services in accordance with Law No. 21 of 2011 concerning the Financial Services Authority (OJK) and Law No. 8 of 1999 concerning Consumer Protection